The Effect of Pre Natal Exercise on Pain and Anxiety Third Pregnancy Primigravida in Sukomoro Public Health Center Magetan - Whida Rahmawati; Nurwijayanti Nurwijayanti; Byba Melda Suhita (Journal for Quality in Public Health, 2020)
The high complaints and discomfort of pregnant women, especially in primigravida third trimester can result in pregnant women experiencing lower back pain due to changes in posture during pregnancy and the existence of anxiety disorders resulting from psychological changes in pregnant women, especially before labor. One of the efforts made to reduce these symptoms could be by doing a pre natal exercise. One of the benefits pre natal exercise is reduce stress in pregnant women and reduce complication especially musculoskeletal problem. The purpose of this study was to analyze the differences in the influence of lower back pain and anxiety of pregnant women before and after the pre natal exercise. This study used a quasi experimental method with one grub pre and post test design research design. The population of this study was all third trimester primigravida pregnant women who participated in pregnancy exercise at Sukomoro Magetan Health Center. The number of samples is 48 respondents. 43,8% pregnant women suffer from moderate pain, and 39,6% pregnants women suffer severe anxiety. Processing and analysis of data using the Wilcoxon test. The results of this study indicate the influence of pre natal exercise on the lowering score of lower back pain by p = 0.003 (<0.005), and the decrease in anxiety scores by p = 0.004 (0.005). The conclusion in this study is the influence of pre natal exercise in reducing lower back pain and anxiety of primigravida third trimester pregnant women